2018
DOI: 10.1515/rjim-2017-0034
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Seminal Plasma Trace Elements on Human Sperm Motility Parameters

Abstract: Elements play major roles in male fertility and directly affect sperm quality. According to the results of this study, the levels of Zn do not affect the sperm quality and motility, while Fe, Cu and Mg are decreased in males with sperm motility problems. Nevertheless, Fe levels can adversely affect sperm motility in normospermic men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 21 publications
1
25
0
2
Order By: Relevance
“…According to El Aaleba's et al findings showed that PE patients had lower levels of seminal plasma Mg levels in comparison to healthy men alongside with similar results about the seminal levels of Mg levels in PE patients. Higher levels of Mg in normozoospermic males compared to asthenozoospermic males were observed in Hashemi's et al results, which can be suspected to affect sperm motility [77].…”
Section: Magnesiummentioning
confidence: 67%
See 1 more Smart Citation
“…According to El Aaleba's et al findings showed that PE patients had lower levels of seminal plasma Mg levels in comparison to healthy men alongside with similar results about the seminal levels of Mg levels in PE patients. Higher levels of Mg in normozoospermic males compared to asthenozoospermic males were observed in Hashemi's et al results, which can be suspected to affect sperm motility [77].…”
Section: Magnesiummentioning
confidence: 67%
“…As far as the copper is concerned, there is a some kind of inconstancy in several trial's findings. Eidi et al [75] and Yan Li et al [76] reported a negative correlation between semen quality and Cu levels (Cu was considered as an environmental chemical pollutant for the workers of the industrial factory in the study of Li et al), whilst in the study of Hashemi et al [77], significantly lower levels of Cu was observed in the seminal fluid of asthenozoospermic subjects in comparison to normozoospermic men not exposed to poisonous amounts of Cu.…”
Section: Coppermentioning
confidence: 99%
“…The excess or the deficiency may lead to defective spermatogenesis and to fertility impairment [6]. About this topic, Hashemi et al [7] reported a negative impact of iron on human sperm motility.…”
Section: Introductionmentioning
confidence: 99%
“…FRA is a glycaemic biomarker used to indicate DM (Lee, 2015) and is associated with the fertilisation process (Tomaszewski et al, 1992). Although imbalances in the biochemical components of seminal plasma have been demonstrated in male with fertility disorders (Hashemi et al, 2018), the alterations of seminal protein markers, MG and FRA in T1DM and T2DM have never been investigated. Many seminal proteins have been identified in different species (stallion: seminal plasma protein 1; cattle: spermadhesin Z13, heparin-binding proteins, osteopontin and phospholipase A2 isoforms; human: stabilin 2, centrosomal proteins, guanine nucleotide-releasing factors and prolactin-inducible proteins) as described previously (Brandon, Heusner, Caudle, & Fayrer-Hosken, 1999;Chacur, 2012;Moura, Koc, Chapman, & Killian, 2006;Yamakawa, Yoshida, Nishikawa, Kato, & Iwamoto, 2007).…”
Section: Introductionmentioning
confidence: 99%